Design and implementation of the corpus of Spanish learners as a foreign language (CAELE) - Ferreira Cabrera, Anita Alejandra; Elejalde Gómez, Jessica; Blanco San Martín, Lorena (Círculo de Lingüística Aplicada a la Comunicación, 2022)
The development of learner corpora has made a significant contribution to Second Language Acquisition (ASL) studies (Granger, 2012, 2015, 2017). The specialized Corpus of Learners of Spanish as a Foreign Language (CAELE) is an open inventory that has 1217 texts produced by 201 learners of different mother tongues and proficiency levels in ELE A2 and B1. Students come from foreign universities in the context of undergraduate and graduate level exchange programs. The collection of texts has been carried out through writing tasks under the task-based methodological approach. This article presents the design, and implementation of the corpus in accordance with the principles of Sinclair (2005). The results show the achievement of a representative and homogeneous corpus to carry out both error analysis and interlanguage contrast studies.